THE CONCEPT OF GENDER: ORIGIN, ESSENCE, FUNCTIONS, AND SOCIAL ROOTS - Bobur Khonturayev (Web of Journals Publishing, 2025)
This article examines the complex idea of gender, investigating its origin, nature, functions, and deeply ingrained societal origins. The research utilizes a multidisciplinary approach to examine the many aspects of gender as a social construct, drawing on findings from sociology, anthropology, psychology, and history. The study conducts a thorough examination of the literature to track the development of gender ideas. It emphasizes how these concepts have changed over time and in different cultures, reflecting larger socio-political shifts and impacting individual identity and social responsibilities. The research uses a qualitative technique to investigate different cultural and historical settings in order to reveal the mechanisms by which gender roles are generated, enacted, and sustained. This text engages in a thorough examination of the jobs assigned to various genders, questioning how these roles originate from and perpetuate societal norms and inequality. The study provides detailed knowledge of how gender is interconnected with cultural practices, legal frameworks, and economic systems. It examines case studies and includes interviews with experts to explore how these factors shape people's experiences and possibilities in society. The results demonstrate that gender is not a fixed or inherent characteristic but rather a flexible concept that adapts to changing social, economic, and political circumstances. The research highlights the need for acknowledging and questioning the deeply embedded societal origins of gender norms to promote a society that is more inclusive and fairer. By doing so, it adds to the continuing discussions in the field of gender studies by offering factual data and theoretical perspectives that emphasize the need for critically reassessing gender as a fundamental element in understanding human social interactions.
Keywords: Gender, genesis, essence, task, social roots, cultural practices, societal norms, identity, historical contexts, gender roles, social construction, intersectionality, feminist theory, masculinity, femininity, gender identity, sexuality, anthropology, sociology, psychology, queer theory, gender studies, patriarchy, gender expression, socialization, and gender equity.